Differences in Prevalence of Refractive Errors in Young Asian Males in Singapore between 1996–1997 and 2009–2010. (August 2014) - Koh, Victor; Yang, Adeline; Saw, Seang Mei; Chan, Yiong Huak; Lin, Sheng Tong; Tan, Mellisa Mei Hui; Tey, Frederick; Nah, Gerard; Ikram, M. Kamran
Abstract Purpose: To determine the differences in prevalence rates of refractive errors in young Singaporean males over a 13-year period between 1996–1997 and 2009–2010 Methods: Non-cycloplegic autorefraction data were obtained in a survey of 15, 085 young male subjects (mean age 19.5 ± 1.4 years, range 16–25 years) in 1996–1997 using a Nikon NRK-8000 autorefractor. A second survey of 28, 908 male subjects (mean age 19.8 ± 1.2 years, range 17–29 years) was conducted in 2009–2010 using a Huvitz MRK-3100 autorefractor. Results: The overall prevalence of myopia (spherical equivalent, SEq, worse than −0.5 diopters, D) was similar in 2009–2010 (81.6%) and 1996–1997 (79.2%; odds ratio 1.38, 95% confidence interval 1.31–1.46; p < 0.001). The prevalence of high myopia (SEq worse than −6.0D) increased from 13.1% in 1996–1997 to 14.7% in 2009–2010 (p < 0.001). The prevalence of refractive astigmatism increased significantly from 41.4% in 1996–1997 to 50.9% in 2009–2010 (p < 0.001). Conclusions: Our results show that the prevalence of myopia and high myopia remained high and the prevalence of astigmatism increased in young male adults in Singapore over a 13-year period after controlling for age, education and ethnicity.